Quality Of Service Saat Tethering Pada Smartphone Android - Guspi Candra; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
With current technological developments, digital equipments have become our daily necessity, one example is an Android Smartphone. In an Android Smartphone device, there are features that can be used to share internet connection, namely Wifi Tethering. Tethering is a Wifi feature in an Android Smartphone that can be used as a mobile hotspot. In fact, the Wifi Tethering feature is still used seldom, because many users’ mobile device still, such as Android Smartphones and Tablet PCs, do not know this feature. These users only use private internet. Therefore, this study discuss using Wifi Tethering on an Android Smartphone. Focus of discussion is to determine one of Qos Parameter, such as Throughput Value, during tethering. This test uses the Wireshark application to monitor the download test process and capture test results. The index results obtained from the Value of Throughput, Delay, Packet Loss are 4 and based on the THIPON Standard it is included in the Very Good Category. For the index result of the jitter value is 3, and based on the THIPON standard it is in the good category.Keywords : Smartphone Android, Tethering, Troughput, Delay, Packet Loss, Jitter.